2021
DOI: 10.1136/archdischild-2020-320540
|View full text |Cite
|
Sign up to set email alerts
|

Strict glycaemic control in very low birthweight infants using a continuous glucose monitoring system: a randomised controlled trial

Abstract: ObjectiveTo evaluate the efficacy of a strict glycaemic control protocol using a continuous glucose monitoring (CGM) in infants at high risk of dysglycaemia with the aim of reducing the number of dysglycaemic episodes.DesignRandomised controlled trial.SettingNeonatal intensive care unit, Fondazione Policlinico Universitario Agostino Gemelli, IRCCS, Rome.PatientsAll infants <1500 g fed on parental nutrition (PN) since birth were eligible. A total of 63 infants were eligible and 48 were randomised.Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The study by Thomson et al showed per cent time in the target range (sensor glucose 2.6-10 mmol/L, 47-180 mg.dl) was greater with CGM than intermittent blood glucose measurement (77% vs. 59%, respectively) and it was highlighted that the CGM also detected clinically unsuspected episodes of hypoglycaemia (23). In the Galderisi study neonates in the unblinded CGM group had a greater percentage of time spent in euglycemic range (median, (24). This highlights the role of CGM in providing clinical teams with the information to allow them to be proactive in management and potentially prevent hypoglycaemia.…”
Section: What Types Of Neonates May Benefit? Pretermmentioning
confidence: 93%
See 3 more Smart Citations
“…The study by Thomson et al showed per cent time in the target range (sensor glucose 2.6-10 mmol/L, 47-180 mg.dl) was greater with CGM than intermittent blood glucose measurement (77% vs. 59%, respectively) and it was highlighted that the CGM also detected clinically unsuspected episodes of hypoglycaemia (23). In the Galderisi study neonates in the unblinded CGM group had a greater percentage of time spent in euglycemic range (median, (24). This highlights the role of CGM in providing clinical teams with the information to allow them to be proactive in management and potentially prevent hypoglycaemia.…”
Section: What Types Of Neonates May Benefit? Pretermmentioning
confidence: 93%
“…The study by Thomson et al showed per cent time in the target range (sensor glucose 2.6–10 mmol/L, 47–180 mg.dl) was greater with CGM than intermittent blood glucose measurement (77% vs. 59%, respectively) and it was highlighted that the CGM also detected clinically unsuspected episodes of hypoglycaemia ( 23 ). In the Galderisi study neonates in the unblinded CGM group had a greater percentage of time spent in euglycemic range (median, 84% vs. 68%, p < .001) and decreased time spent in mild ( p = .04) and severe ( p = .007) hypoglycaemia compared with the blinded CGM group ( 24 ). The study by Perri et al, showed that using CGM alarms for stricter target thresholds of glucose control (3.44–7.78 mmol/L, 62–140 mg/dl) combined with 33% dextrose infusion, as needed, compared to the use of CGM set to more conventional glucose thresholds (2.61–10 mmol/L, 47–180 mg/dl) resulted in significantly less dysglycaemia ( 24 ).…”
Section: What Types Of Neonates May Benefit?mentioning
confidence: 97%
See 2 more Smart Citations
“…Lastly, although preterm infants experience a greater number of skin breaks than the average term infant, newborns with hypoglycemia are often exposed to many skin breaks a day from repeated point of care glucose measurements. Recent literature has demonstrated that continuous glucose measurement through subcutaneously implanted devices is both accurate and can help reduce such testing to a couple occurrences a day for calibration in both the preterm and term populations with hypoglycemia ( 11 , 12 ).…”
mentioning
confidence: 99%